Gambaran pengetahuan, sikap, dan tindakan mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi terhadap kesiapsiagaan bencana alam - Nahdiyah Taha; Ronald I. Ottay; Windy Mariane Virenia Wariki (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2022)
Natural disasters are frequent events in Indonesia. The occurrence of natural disasters will result in various kinds of damage, losses, and even health problems. Lack of knowledge about disaster preparedness will affect a person's attitude and actions in dealing with disasters. It takes special expertise of medical students who will become a competent doctor in health services during natural disasters. This study aims to determine the description of knowledge, attitudes, and actions of students of the Medical Education Study Program, Faculty of Medicine, Sam Ratulangi University towards natural disaster preparedness. This is a descriptive study with a cross sectional design with a sampling technique using simple random sampling. The research instrument used a questionnaire (Google form). Total respondents who participated in this study were 116 respondents. The results showed that Medical Education students of the Faculty of Medicine, Sam Ratulangi University mostly had high knowledge of disaster preparedness as much as 61.2%, a positive attitude towards disaster preparedness as much as 63.8%, and were able to take action on disaster preparedness as much as 71.6%. From the result of this study, it can be concluded that Medical Education Students of the Faculty of Medicine, Sam Ratulangi University have high levels of knowledge, positive attitudes, and capable actions in natural disaster preparedness. Keywords: Disaster preparedness, knowledge, attitude, practice